A young star-forming galaxy at z = 3.5 with an extended Lyman α halo seen with MUSE. Issue 4 (13th January 2016) - Patrício, Vera; Richard, Johan; Verhamme, Anne; Wisotzki, Lutz; Brinchmann, Jarle; Turner, Monica L.; Christensen, Lise; Weilbacher, Peter M.; Blaizot, Jérémy; Bacon, Roland; Contini, Thierry; Lagattuta, David; et al.
Abstract: Spatially resolved studies of high-redshift galaxies, an essential insight into galaxy formation processes, have been mostly limited to stacking or unusually bright objects. We present here the study of a typical ( L *, M ⋆ = 6 × 10 9  M⊙ ) young lensed galaxy at z = 3.5, observed with Multi Unit Spectroscopic Explorer (MUSE), for which we obtain 2D resolved spatial information of Lyα and, for the first time, of C iii ] emission. The exceptional signal-to-noise ratio of the data reveals UV emission and absorption lines rarely seen at these redshifts, allowing us to derive important physical properties ( T e ∼ 15600 K, n e  ∼ 300 cm −3, covering fraction f c ∼ 0.4) using multiple diagnostics. Inferred stellar and gas-phase metallicities point towards a low-metallicity object ( Z stellar = ∼0.07 Z⊙ and Z ISM  < 0.16 Z⊙ ). The Lyα emission extends over ∼10 kpc across the galaxy and presents a very uniform spectral profile, showing only a small velocity shift which is unrelated to the intrinsic kinematics of the nebular emission. The Lyα extension is approximately four times larger than the continuum emission, and makes this object comparable to low-mass LAEs at low redshift, and more compact than the Lyman-break galaxies and Lyα emitters usually studied at high redshift. We model the Lyα line and surface brightness profile using a radiative transfer code in an expanding gas shell, finding that this model provides a good description of both observables.